Analgesic protocol for procedural pain treatment of second-degree burns in children - Komarčević, Aleksandar; Jokić, Radoica; Pajić, Miloš; Jovanović, Mladen; Milenković, Marina (Vojnosanitetski pregled, 2023)
Background/Aim. Children with burns are submitted to multiple painful and anxiety-related procedures during the change of wound dressing, treatment, and rehabilitation. The objective of analgesic treatments for procedural pain is the safe and efficient management of pain and emotional stress, which requires a careful, balanced, and systematic approach. The aim of this study was to determine the effec-tiveness of analgesic and/or local anesthetic in relieving the intensity of procedural pain. Methods. The study included 120 pediatric patients with second-degree burns who were allocated into four groups of 30 children (control group, groups I, II, and III). During the change of wound dress-ings, children in the control group did not receive any anal-gesics, while in the remaining three groups, 30 minutes prior to the change of wound dressing, oral nonsteroidal anti-inflammatory drug (group I), local anesthetic (group II), or both medications (group III) were administered. Results. The average visual analog scale (VAS) score for assessing pain was statistically significantly higher in the control group on all tested days compared with children in the other three treated groups. On the first test day (24 hrs after sustaining the burn injuries), all children had high VAS scores, and ac-cording to the receiver operating characteristics (ROC) analysis, the boundary value was 89.50/100. There was a remarkable difference in the VAS score between the groups on the fifth day of dressing change with the boundary value of 57.50/100 and on the seventh day when the boundary value was 43.50/100. Children who experienced the lowest intensity pain during dressing changes of burn wounds for all test days were those from the group who received both systemic analgesic and local anesthetic. Conclusion. The study confirmed the importance of introducing the complex polymodal protocol in treating procedural pain in second-degree burns. The protocol should include analgesics as well as anesthetics since they both contribute to achieving the best results in pain reduction and treatment outcomes.
Keywords: analgesics; anesthetics, local; burns; child; pain measurement